Services écologiques et Trame Verte Urbaine - Philippe Clergeau (VertigO)
The importance of nature role in cities is underlined here through the ecological services applied at the urban system (production, regulation, cultural). The biodiversity is the heart of these relationships and is directly under the influence of climatology. At a holistic scale, we can underline the relation between the geographical change in reproductive areas of species with the recent climate change and the barrier effect of cities in these dispersions. Settlement of green framework in megacity can permit not only to refresh the city but also can give transparency at urban areas for species movements.